2005
DOI: 10.2337/diacare.28.7.1562
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rosiglitazone on Overweight Subjects With Type 1 Diabetes

Abstract: OBJECTIVE -To evaluate the safety and effectiveness of rosiglitazone in the treatment of overweight subjects with type 1 diabetes.RESEARCH DESIGN AND METHODS -A total of 50 adult type 1 diabetic subjects with a baseline BMI Ն27 kg/m 2 were randomly assigned in a double-blind fashion to take insulin and placebo (n ϭ 25) or insulin and rosiglitazone 4 mg twice daily (n ϭ 25) for a period of 8 months. Insulin regimen and dosage were modified in all subjects to achieve near-normal glycemic control.RESULTS -Both gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 30 publications
1
32
0
4
Order By: Relevance
“…Probably, TZD treatment is only associated with decreased insulin in patients already showing elevated plasma concentrations. This was also seen in patients with type 1 diabetes, where the greatest improvements in glycemic control with combined rosiglitazone and insulin treatment were seen in those patients with more pronounced markers of insulin resistance [30].…”
Section: Discussionmentioning
confidence: 65%
“…Probably, TZD treatment is only associated with decreased insulin in patients already showing elevated plasma concentrations. This was also seen in patients with type 1 diabetes, where the greatest improvements in glycemic control with combined rosiglitazone and insulin treatment were seen in those patients with more pronounced markers of insulin resistance [30].…”
Section: Discussionmentioning
confidence: 65%
“…Destaca-se, entretanto, que, nesta situação, a utilização de agentes sensibilizadores à insulina talvez mereça ser considerada, em conjunto com ênfase em mudanças no estilo de vida, de forma a contribuir para uma melhora no perfil metabó-lico desses pacientes (18).…”
Section: Discussionunclassified
“…22 A recent randomized placebo-controlled study of adults with T1D and rosiglitazone as adjunctive therapy demonstrated no significant difference in rates of hypoglycemia but increased rates of edema and anemia in the thiazolidinediones-treated group. 13 Further evaluation of safety is indicated in T1D because of small study patient numbers.…”
Section: Discussionmentioning
confidence: 99%
“…10-12 A recent placebo-controlled trial of rosiglitazone in conjunction with standard care in adults with type 1 diabetes showed similar improvements in A1c in the groups but with less insulin required in the rosiglitazone-treated compared with the placebo group. 13 The mechanism of action of thiazolidinediones on metabolic control is primarily through enhancement of peripheral glucose utilization with some suppression of hepatic glucose production. 12 Adolescents with type 1 diabetes have reduced peripheral insulin sensitivity as measured by hyperinsulinemic-euglycemic clamp studies.…”
mentioning
confidence: 99%